Composite material, method for its production, use and secondary battery cell
Patent Information
- Application Number
- CN202510417580.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]目前,二次电芯中的很多零件都是由塑料制成,塑料的导热性较差,导热系数一般≤0.19W/m·K,而卷芯外侧的铝壳的导热系数一般约为237W/m·K
[0031]The composite material provided by this invention optimizes the synergistic design of the polymer matrix (PC, PET, PP) and thermally conductive particles. In this invention, thermally conductive particles are added to the polymer matrix, increasing the thermal conductivity of the polymer matrix without compromising its insulation properties. The silane coupling agent improves the compatibility between the thermally conductive particles and the polymer matrix through chemical bonding (reaction of -NH with -OH on the surface of the thermally conductive particles); it also reduces the surface energy of the thermally conductive particles, improves dispersion uniformity, inhibits agglomeration, and reduces interfacial thermal resistance. By combining the above components in specific amounts, a synergistic thermally conductive network can be formed, increasing the thermal conductivity to 0.5–2 W/m·K while ensuring a volume resistivity >10¹ Ω·cm. This invention further defines the preparation method of the composite material. Pretreatment of the thermally conductive particles enhances the compatibility between the particles and the polymer matrix and ensures stepwise blending, avoiding the formation of conductive pathways. Furthermore, the passivation layer improves resistance to electrolyte corrosion. The resulting composite material can be widely used in the manufacture of parts for secondary battery cells. It is particularly suitable for manufacturing at least one of the following parts: Mylar film, base plate, lower plastic, insulating film, battery cell insulating tape, and top patch.
Smart Images

Figure CN122917435A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a composite material, its preparation method, its application, and a secondary battery cell. Background Technology
[0002] Existing secondary battery cells have the following basic structure and component composition: Figure 1 As shown, from top to bottom, it includes a top patch, a top cover, a core, and a bottom support plate. The top cover includes a top cover sheet and a lower plastic sheet. The outer side of the core is covered with Mylar film, an aluminum shell, and an insulating film. The core is provided with insulating tape for fixing, insulating, and heat transfer.
[0003] Currently, many components in secondary battery cells are made of plastic. Plastic has poor thermal conductivity, typically ≤0.19 W / m·K, while the thermal conductivity of the aluminum shell on the outer side of the core is generally around 237 W / m·K. This results in the plastic components having a much lower thermal conductivity than the aluminum shell, leading to insufficient heat dissipation. When the battery cell operates at high rates or overheats under other conditions, it cannot efficiently dissipate internal heat to ensure normal and safe operation. Furthermore, in low temperatures such as winter, it cannot promptly transfer the heat generated by the module into the battery cell, preventing it from operating at its optimal temperature.
[0004] Currently, there are technologies to dope plastics to improve thermal conductivity, but current doping techniques are prone to problems such as decreased insulation or filler agglomeration and aging.
[0005] In view of this, the present invention is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a composite material, its preparation method, its application, and a secondary battery cell.
[0007] This invention is implemented as follows:
[0008] In a first aspect, the present invention provides a composite material comprising a polymer matrix, thermally conductive particles, and a silane coupling agent.
[0009] In an optional embodiment, the mass percentage of the thermally conductive particles is 28%-55%;
[0010] And / or, the thermal conductivity of the composite material is 0.5 to 2 W / m·K; preferably 0.5 to 1.3 W / m·K;
[0011] And / or, the polymer matrix includes at least one of PP, PET and PC;
[0012] And / or, the thermally conductive particles include one or more of boron nitride, aluminum oxide, graphene, aluminum nitride, silicon nitride, silicon carbide, magnesium oxide, zinc oxide, barium titanate, cerium dioxide, Sr2ZnSi2O7, TiC, TiO2, and Al(OH)3.
[0013] In an optional embodiment, the thermally conductive particles include boron nitride, aluminum oxide, and graphene, wherein the graphene is fluorinated graphene; the composite material comprises, by mass percentage, 50%-70% polymer matrix, 20-30% boron nitride, 5%-15% aluminum oxide, 3%-10% fluorinated graphene, and 1%-3% silane coupling agent.
[0014] In an optional embodiment, the boron nitride is in the form of flakes with a particle size of 1-5 μm;
[0015] And / or, the alumina is spherical with a particle size of 0.5-2 μm;
[0016] And / or, the C / F ratio of the fluorinated graphene is ≥4:1, and the thickness of the fluorinated graphene is 1-5 nm;
[0017] And / or, the volume resistivity of the composite material is >101 Ω·cm.
[0018] In a second aspect, the present invention provides a method for preparing a composite material, which includes melting and blending the components of the composite material as described in any of the foregoing embodiments, then extruding and pressing the mixture into shape, and subjecting the shaped sample to plasma treatment to form a passivation layer.
[0019] In an optional embodiment, before the melt blending, the thermally conductive particles are further pretreated: the thermally conductive particles are first mixed and dried to obtain a dried material, and then the dried material is coated with a solution of the silane coupling agent to obtain a premix.
[0020] Preferably, the drying process includes drying at 110-130°C for 3-5 hours.
[0021] In an optional embodiment, the melt blending includes: feeding the polymer matrix and the premix into a twin-screw extruder for melting;
[0022] Preferably, the screw speed of the twin-screw extruder is 200-300 rpm;
[0023] Preferably, the twin-screw extruder is provided with a feeding section, a melting section and a mixing section, wherein the temperature of the feeding section is 180-250℃, the temperature of the melting section is 200-280℃, and the temperature of the mixing section is 190-260℃;
[0024] Preferably, when the thermally conductive particles include boron nitride, aluminum oxide, and fluorinated graphene, the boron nitride and aluminum oxide are first mixed and dried to obtain a dried material, and the dried material is coated with a solution of the silane coupling agent to obtain a premix; then the polymer matrix and the premix are fed into a twin-screw extruder for melting, and then the fluorinated graphene is added in multiple batches for melt blending.
[0025] In an optional embodiment, the pressing temperature is 180-250℃, the pressure is 10-20MPa, and the holding time is 5-10min.
[0026] In an optional embodiment, the plasma treatment includes treating with Ar gas at a power of 80-120W for 4-6 minutes to generate a passivation layer of 5-10 nm.
[0027] Thirdly, the present invention provides the application of the composite material as described in any of the foregoing embodiments or the composite material prepared by the method described in any of the foregoing embodiments in the preparation of parts for secondary battery cells.
[0028] In an optional embodiment, the components of the secondary battery cell include at least one of Mylar film, bottom plate, lower plastic, insulating film, battery cell insulating tape, and top patch; the thermal conductivity of the composite material is 0.5 to 2 W / m·K.
[0029] Fourthly, the present invention provides a secondary battery cell, which comprises, from top to bottom, a top patch, a top cover, a core, and a bottom support plate. The outer side of the core is sequentially covered with a Mylar film, an aluminum shell, and an insulating film. The core is provided with a battery cell insulating tape for fixing, insulating, and heat transfer. The top cover comprises a top cover sheet and a lower plastic sheet. At least one of the Mylar film, bottom support plate, lower plastic sheet, insulating film, battery cell insulating tape, and top patch is made of a composite material as described in any of the foregoing embodiments.
[0030] The present invention has the following beneficial effects:
[0031] The composite material provided by this invention optimizes the synergistic design of the polymer matrix (PC, PET, PP) and thermally conductive particles. In this invention, thermally conductive particles are added to the polymer matrix, increasing the thermal conductivity of the polymer matrix without compromising its insulation properties. The silane coupling agent improves the compatibility between the thermally conductive particles and the polymer matrix through chemical bonding (reaction of -NH with -OH on the surface of the thermally conductive particles); it also reduces the surface energy of the thermally conductive particles, improves dispersion uniformity, inhibits agglomeration, and reduces interfacial thermal resistance. By combining the above components in specific amounts, a synergistic thermally conductive network can be formed, increasing the thermal conductivity to 0.5–2 W / m·K while ensuring a volume resistivity >10¹ Ω·cm. This invention further defines the preparation method of the composite material. Pretreatment of the thermally conductive particles enhances the compatibility between the particles and the polymer matrix and ensures stepwise blending, avoiding the formation of conductive pathways. Furthermore, the passivation layer improves resistance to electrolyte corrosion. The resulting composite material can be widely used in the manufacture of parts for secondary battery cells. It is particularly suitable for manufacturing at least one of the following parts: Mylar film, base plate, lower plastic, insulating film, battery cell insulating tape, and top patch. Attached Figure Description
[0032] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 This is a schematic diagram of the structure of the secondary battery provided by the present invention;
[0034] Figure 2 This is a schematic diagram of the top cover structure in the secondary battery provided by the present invention;
[0035] Figure 3 This is a schematic diagram of the structure of the secondary battery provided by the present invention when the winding core and the bottom support plate are assembled.
[0036] Figure 4 This is a schematic diagram of the structure of the cell insulating tape in the core of the secondary battery provided by the present invention.
[0037] Figure 5 A process flow diagram illustrating the preparation method of the insulating high thermal conductivity composite material provided by the present invention;
[0038] Figure 6 This is a graph showing the relationship between the cell temperature drop and the thermal conductivity of the insulating component at different rates, as provided in Experimental Example 1 of this invention.
[0039] Figure 7 The graph shows the relationship between the average temperature of the battery cell and the thermal conductivity of the insulation component at different rates, as provided in Experimental Example 1 of this invention.
[0040] Icons: 100-Secondary battery; 110-Top patch; 120-Top cover; 121-Adapter; 122-Top cover; 123-Lower plastic; 124-Explosion-proof valve protective patch; 125-Negative electrode upper plastic; 126-Positive electrode upper plastic; 127-Explosion-proof valve; 128-Sealing ring; 129-Terminal post; 130-Core; 131-Mylar film; 132-Aluminum shell; 133-Insulating film; 134-Cell insulating tape; 140-Bottom plate. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0042] This invention improves the materials of the components of the secondary battery 100, especially the plastic components. To more clearly describe the location of the plastic components of the secondary battery 100, this invention first describes the basic structure of the existing secondary battery 100.
[0043] Please see Figure 1 ,from Figure 1 As can be seen, the secondary battery 100 includes, from top to bottom, a top patch 110, a top cover 120, a core 130, and a bottom support plate 140. The top patch 110 and top cover 120 are also for the functions of sealing, connection, and safety of the battery. A plastic sealing pin (not shown) and an aluminum sealing pin (not shown) are provided between the top patch 110 and the top cover 120. The plastic sealing pin and the aluminum sealing pin are components on the top cover 120. The plastic sealing pin mainly functions to seal, insulate, and prevent short circuits in the electrolyte cavity, while the aluminum sealing pin mainly functions to reinforce the structure, seal, and provide electrical connection. Please refer to [link to relevant documentation]. Figure 2 The top cover 120 includes a top cover sheet 122 and a lower plastic sheet 123. The top cover sheet 122 also has a negative electrode upper plastic sheet 125, a positive electrode upper plastic sheet 126, and an explosion-proof valve protection patch 124. An explosion-proof valve 127 is also provided on the lower plastic sheet 123. Below the lower plastic sheet 123 are two sealing rings 128 and two terminals 129 (e.g., negative terminal 129 and positive terminal 129). An adapter piece 121 (e.g., aluminum adapter piece 121 and copper adapter piece 121) is provided between the top cover 120 and the core 130. The bottom support plate 140 is an important support component at the bottom of the battery, mainly responsible for mechanical support, electrical connection, heat dissipation, and safety protection. Please refer to [link to relevant documentation]. Figure 1 and Figure 3 The outer side of the core 130 is sequentially covered with a Mylar film 131, an aluminum shell 132, and an insulating film 133. The Mylar film 131 has high strength, high temperature resistance, and insulation properties, and is mainly used for external protection of the core 130. The aluminum shell 132 is the metal shell of a square or cylindrical battery (such as 18650, power battery), usually made of aluminum alloy (such as 3003, 6063), balancing lightweight and strength. It forms a sealed space with the top cover 120 and the bottom support plate 140 through laser welding to prevent electrolyte leakage and moisture / oxygen intrusion. At the same time, it provides high-strength protection for the core 130, preventing the core 130 from being deformed by external pressure. In addition, the high thermal conductivity of aluminum alloy helps to quickly conduct heat from inside the cell to the outside, avoiding local overheating. The insulating film 133 is used for insulation between the cell and the shell / tab. The core 130 is provided with cell insulating tape 134 for fixing, insulating, and heat transfer. Figure 4 (As shown), in addition, the battery core insulating tape 134 can also be set at other conventional positions of the core 130. The specific setting position is not described in detail in this invention, but can be referred to in the existing process.
[0044] In the above structure, the Mylar membrane 131, the base plate 140, the lower plastic 123, the insulating film 133, the battery cell insulating tape 134, and the top patch 110 are all made of plastic, also referred to as plastic parts. Specifically, the Mylar membrane 131, the base plate 140, and the lower plastic 123 are usually made of PP plastic, while the insulating film 133 and the battery cell insulating tape 134 are mostly made of PET plastic + adhesive material, and the top patch 110 is mostly made of PC plastic + adhesive material.
[0045] All of these plastic parts have poor thermal conductivity, with a thermal conductivity generally ≤0.19W / m·K. When the battery cell is operating at high rates or when it overheats internally, they cannot efficiently dissipate internal heat to ensure the normal and safe operation of the battery cell. When the temperature is low, such as in winter, they cannot transfer the heat from the module to the battery cell into the battery cell in time, so that the battery cell can operate at the most suitable temperature.
[0046] In some embodiments, composite materials made of plastics and high thermal conductivity materials are used. However, the thermal conductivity of these composite materials is high, typically greater than 2 W / m·K, and can even reach 30 W / m·K. Since the main purpose of using plastic in the secondary battery 100 is to prevent the propagation of thermal runaway, the battery may experience thermal runaway under overcharging, short circuit, or high-temperature conditions, generating a large amount of heat. Plastics with low thermal conductivity can slow the transfer of heat from the cell to the bottom of the battery, preventing rapid spread of thermal runaway throughout the entire battery pack (especially in modules). High thermal conductivity materials such as metals accelerate heat diffusion, increasing the risk of a chain reaction of thermal runaway between adjacent cells. Furthermore, plastic parts have natural insulation properties, eliminating the need for additional insulation layers, simplifying the structure and reducing costs. However, if the thermal conductivity of plastic parts is too high, an insulating film 133 (such as PET) needs to be added, but this may fail due to mechanical damage. In addition, the cell expands / contracts during charging and discharging; the high rigidity of metal parts may exacerbate internal stress. Plastic parts, on the other hand, have a certain degree of elasticity and can absorb some of the expansion stress, reducing the risk of cell deformation. Electrolytes are corrosive, while plastic parts are corrosion-resistant. However, metal parts may rust or oxidize after prolonged contact with the electrolyte, leading to increased contact resistance.
[0047] Therefore, this invention provides an insulating and highly thermally conductive composite material. By optimizing the synergistic design of the polymer matrix (PC, PET, PP) and thermally conductive particles, the thermal conductivity is increased to 0.5–2 W / m·K while ensuring a volume resistivity >10¹ Ω·cm. The specific technical solution is as follows:
[0048] The present invention provides a composite material whose components, by mass percentage, include a polymer matrix, thermally conductive particles and a silane coupling agent.
[0049] In this invention, thermally conductive particles are used as fillers to form a synergistic thermally conductive network structure with the polymer matrix. The thermal conductivity of the composite material is 0.5–2 W / m·K; preferably 0.5–1.3 W / m·K.
[0050] The polymer matrix comprises 50%-70% by mass. This proportion ensures the formation of a continuous phase in the polymer matrix and avoids a decrease in mechanical properties due to excessive thermally conductive particles. The polymer matrix includes, but is not limited to, at least one of PP, PET, and PC.
[0051] The mass percentage of thermally conductive particles is 28%-55%, and the thermally conductive particles include, but are not limited to, one or more of boron nitride, aluminum oxide, graphene, aluminum nitride, silicon nitride, silicon carbide, magnesium oxide, zinc oxide, barium titanate, cerium dioxide, Sr2ZnSi2O7, TiC, TiO2, and Al(OH)3.
[0052] Preferably, the thermally conductive particles include boron nitride, aluminum oxide, and graphene, wherein the graphene is fluorinated graphene. In this case, the composite material comprises, by mass percentage, 50%-70% polymer matrix, 20-30% boron nitride, 5%-15% aluminum oxide, 3%-10% fluorinated graphene, and 1%-3% silane coupling agent.
[0053] Boron nitride (BN) is used as the main filler. It is in the form of flakes with a particle size of 1-5 μm. The mass percentage of boron nitride is 20%-30%, which is close to the penetration threshold (about 25%). It can form a continuous thermally conductive network without damaging the insulation. The present invention found that when the amount of boron nitride exceeds 30%, it may lead to an increase in interfacial thermal resistance or excessive cost.
[0054] Alumina (AlO) is used as an auxiliary filler. It is spherical with a particle size of 0.5-2μm. The mass percentage of alumina is 5%-15%. This amount can balance cost and performance. If it is less than 5%, it will not reduce boron nitride agglomeration and improve dispersion uniformity. If it exceeds 15%, it may cause interface defects due to particle size differences.
[0055] In some embodiments, the C / F ratio of fluorinated graphene (F-Graphene) is ≥4:1, and the thickness of the fluorinated graphene is 1-5 nm. Fluorinated graphene is beneficial for suppressing the conductivity of graphene. Fluorination introduces CF bonds, disrupting the conjugated structure of graphene and making it an insulator (resistivity >10¹² Ω·cm), suitable for applications requiring insulation and high thermal conductivity. Its content is 3%-10%. This invention has found that when the content of fluorinated graphene is below 3%, the effect of reducing the thermal resistance at the interface between the thermally conductive particles and the substrate may be poor, and when it exceeds 10%, incomplete fluorination may occur, resulting in insulation failure in the residual conductive graphene regions. The fluorinated graphene in this invention can be prepared in-house or commercially available. When prepared in-house, the method includes fluorination modification of the graphene surface by chemical vapor deposition (CVD), with a surface fluorine content ≤15% to maintain insulation. It should be understood that other conventional preparation methods can also be used to prepare fluorinated graphene, as long as they meet the requirements of the fluorinated graphene in this invention.
[0056] Silane coupling agents can improve the compatibility of BN / AlO with the polymer matrix through chemical bonding (reaction of -NH with -OH on the surface of thermally conductive particles); simultaneously, they can reduce the surface energy of thermally conductive particles, improve dispersion uniformity, inhibit agglomeration, and reduce interfacial thermal resistance. A dosage of 1%–3% silane coupling agent is sufficient to cover the active sites on the surface of thermally conductive particles; excessive amounts may lead to matrix plasticization or decreased thermal stability. For example, 2% silane coupling agent can increase interfacial bonding strength by approximately 30%.
[0057] In addition, the present invention provides a method for preparing a composite material, which includes melting and blending the components of the composite material as described above, then extruding and pressing them into shape, and subjecting the shaped sample to plasma treatment to form a passivation layer.
[0058] Specifically, please refer to Figure 5 It includes the following steps:
[0059] S1, Preprocessing.
[0060] First, the heat-conducting particles are mixed and dried to obtain a dried material. Then, the dried material is coated with a silane coupling agent solution to obtain a premix. The drying process involves drying at 110-130℃ for 3-5 hours.
[0061] When the thermally conductive particles include boron nitride, aluminum oxide, and fluorinated graphene, the coating of red galvanic acid and silane coupling agents can be applied only to boron nitride and aluminum oxide.
[0062] S2, melt blending.
[0063] The polymer matrix and premix are fed into a twin-screw extruder for melting;
[0064] Preferably, the screw speed of the twin-screw extruder is 200-300 rpm;
[0065] Preferably, the twin-screw extruder is equipped with a feeding section, a melting section, and a mixing section. The feeding section aims to stably convey raw materials, uniformly introducing solid materials (such as plastic granules, powders, or thermally conductive particles) from the hopper into the extruder to ensure continuous feeding. The screw's spiral propulsion reduces gaps between materials, preparing them for subsequent melting. The temperature of the feeding section is 180-250°C. The melting section primarily aims to melt the solid materials into a viscous flow state through shear heat and external heating. Simultaneously, the screw channel depth gradually decreases in the melting section, facilitating material compression and expelling entrained air or volatiles (such as moisture). In this invention, the temperature of the melting section is 200-280°C. The mixing section aims to ensure that the various components of the melt (such as base material, additives, and thermally conductive particles) are fully dispersed and distributed, achieving homogenization. Simultaneously, the mixing section can also generate stretching and shearing actions, breaking up agglomerates and achieving uniform mixing. In this invention, the temperature of the mixing section is 190-260°C. By rationally designing these three sections, the twin-screw extruder can efficiently complete complex tasks such as compounding, modification, and reactive extrusion. Furthermore, in this invention, the polymer matrix, premix, and fluorinated graphene are all added in the feeding section, but the fluorinated graphene is added in multiple stages to ensure gradual dispersion and blending, thus avoiding the formation of conductive pathways.
[0066] It should also be noted that the specific temperatures of the feeding section, melting section, and mixing section in this invention are closely related to the choice of polymer matrix. When superior corrosion resistance of the composite material is required, PP can be selected as the polymer matrix; when superior temperature resistance is required, PET can be selected as the polymer matrix; and when superior overall performance is required, PC can be selected as the polymer matrix. When PP is selected as the polymer matrix, the temperature of the feeding section can be, for example, around 180°C, the temperature of the melting section can be, for example, around 200°C, and the temperature of the mixing section can be, for example, around 190°C. When PET or PC is selected as the polymer matrix, the temperature of the feeding section can be, for example, around 250°C, the temperature of the melting section can be, for example, around 280°C, and the temperature of the mixing section can be, for example, around 260°C.
[0067] S3, compression molding.
[0068] The extruded samples are then compressed into shape. The compression molding temperature is 180-250℃, the pressure is 10-20MPa, and the holding time is 5-10min. The molding temperature is also related to the choice of polymer matrix. When PP is selected as the polymer matrix, the compression molding temperature is around 180℃; when PET is selected as the polymer matrix, the compression molding temperature is around 250℃; and when PC is selected as the polymer matrix, the compression molding temperature is around 240℃.
[0069] S4, Post-processing.
[0070] The molded sample is subjected to plasma treatment to form a passivation layer. This plasma treatment involves treating the sample with Ar gas at a power of 80-120W for 4-6 minutes to generate a passivation layer of 5-10 nm. In this invention, an inert gas, such as Ar, is used to provide an inert atmosphere for plasma treatment. The resulting passivation layer effectively prevents subsequent oxidation of the composite material. Furthermore, the passivation layer further enhances the insulation effect. In this invention, passivation can clean some organic contaminants and weakly bonded impurities from the surface, while simultaneously forming a rough passivation layer that enhances corrosion resistance and reduces interfacial defects, thus lowering interfacial thermal resistance.
[0071] The composite material provided by this invention optimizes the synergistic design of the polymer matrix (PC, PET, PP) and thermally conductive particles. By adding thermally conductive particles to the polymer matrix, a synergistic thermally conductive network can be formed. Furthermore, the interfacial thermal resistance is reduced by utilizing a silane coupling agent to react with the polymer chains. While ensuring a volume resistivity >10¹ Ω·cm, the thermal conductivity is increased to 0.5–2 W / m·K. The prepared composite material can be widely used in the manufacture of components for secondary battery cells. It is particularly suitable for the manufacture of at least one of the following components: Mylar film 131, base plate 140, lower plastic 123, insulating film 133, battery cell insulating tape 134, and top patch 110.
[0072] Correspondingly, the present invention also provides a secondary battery cell, which includes, from top to bottom, a top patch 110, a top cover 120, a core 130, and a bottom support plate 140. The outer side of the core 130 is covered with a Mylar film 131, an aluminum shell 132, and an insulating film 133. The core 130 is provided with a battery cell insulating tape 134 for fixing, insulating, and heat transfer. The top cover 120 includes a top cover sheet 122 and a lower plastic sheet 123. At least one of the Mylar film 131, the bottom support plate 140, the lower plastic sheet 123, the insulating film 133, the battery cell insulating tape 134, and the top patch 110 is made of the above-mentioned composite material.
[0073] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0074] Example 1
[0075] This embodiment provides a composite material comprising 60% polymer matrix PP, 25% boron nitride, 10% alumina, 3% fluorinated graphene, and 2% silane coupling agent KH550.
[0076] Its preparation methods include:
[0077] S1. Pretreatment: First, mix boron nitride and aluminum oxide and dry them at 120°C for 4 hours to obtain dried material. Then, coat the dried material with an ethanol solution (concentration 2%) of silane coupling agent, dry it at 60°C, and ball mill it to obtain premixed material.
[0078] S2. Melt Blending: The polymer matrix and premix are fed into a twin-screw extruder for melting, and then fluorinated graphene is added in multiple batches for melt blending; the screw speed of the twin-screw extruder is 250 rpm; the temperature of the feeding section of the twin-screw extruder is 180℃, the temperature of the melting section is 200℃, and the temperature of the mixing section is 190℃.
[0079] S3. Compression molding: The extruded product is molded. The compression molding temperature is 180℃, the pressure is 15MPa, and the holding time is 8min.
[0080] S4. Post-treatment: The molded sample is subjected to plasma treatment with Ar gas at a power of 100W for 5 minutes to form an 8nm passivation layer.
[0081] Example 2
[0082] This embodiment provides a composite material comprising 55% of a polymer matrix PET and PC (50:50), 30% boron nitride, 10% alumina, 3% fluorinated graphene, and 2% silane coupling agent.
[0083] Its preparation methods include:
[0084] S1. Pretreatment: First, mix boron nitride and aluminum oxide and dry them at 120°C for 4 hours to obtain dried material. Then, coat the dried material with an ethanol solution (concentration 2%) of silane coupling agent, dry it at 60°C, and ball mill it to obtain premixed material.
[0085] S2. Melt Blending: The polymer matrix and premix are fed into a twin-screw extruder for melting, and then fluorinated graphene is added in multiple batches for melt blending; the screw speed of the twin-screw extruder is 250 rpm; the temperature of the feeding section of the twin-screw extruder is 250℃, the temperature of the melting section is 280℃, and the temperature of the mixing section is 260℃.
[0086] S3. Compression molding: The extruded product is molded. The compression molding temperature is 250℃, the pressure is 15MPa, and the holding time is 8min.
[0087] S4. Post-treatment: The molded sample is subjected to plasma treatment with Ar gas at a power of 100W for 5 minutes to form an 8nm passivation layer.
[0088] Example 3
[0089] This embodiment provides a composite material comprising 66% PET polymer matrix, 20% boron nitride, 5% alumina, 6% fluorinated graphene, and 3% silane coupling agent.
[0090] Its preparation methods include:
[0091] S1. Pretreatment: First, mix boron nitride and aluminum oxide and dry them at 110℃ for 5 hours to obtain dried material. Then, coat the dried material with an ethanol solution (concentration 3%) of silane coupling agent, dry it at 50℃, and then ball mill and mix it to obtain premix.
[0092] S2. Melt Blending: The polymer matrix and premix are fed into a twin-screw extruder for melting, and then fluorinated graphene is added in multiple batches for melt blending; the screw speed of the twin-screw extruder is 250 rpm; the temperature of the feeding section of the twin-screw extruder is 250℃, the temperature of the melting section is 280℃, and the temperature of the mixing section is 260℃.
[0093] S3. Compression molding: The extruded product is molded. The compression molding temperature is 250℃, the pressure is 20MPa, and the holding time is 5min.
[0094] S4. Post-treatment: The molded sample is subjected to plasma treatment with Ar gas at a power of 80W for 6 minutes to form a 10nm passivation layer.
[0095] Example 4
[0096] This embodiment provides a composite material comprising 60% PP polymer matrix, 25% aluminum nitride, 10% silicon nitride, 3% cerium dioxide, and 2% silane coupling agent KH550. Its preparation method is the same as in Example 1.
[0097] Example 5
[0098] This embodiment provides a composite material comprising a polymer matrix of 60% PP, 25% Sr2ZnSi2O7, 10% Al(OH)3, 3% TiC, and 2% silane coupling agent KH550. Its preparation method is the same as in Example 1.
[0099] Comparative Example 1
[0100] This comparative example is basically the same as Example 1, except that fluorinated graphene is omitted in this comparative example. The components in this comparative example include 63% PP polymer matrix, 25% boron nitride, 10% alumina and 2% silane coupling agent.
[0101] Comparative Example 2
[0102] This comparative example is basically the same as Example 1, except that boron nitride and aluminum oxide are omitted in this comparative example. In this comparative example, the components include 95% polymer matrix PP, 3% fluorinated graphene and 2% silane coupling agent.
[0103] Comparative Example 3
[0104] This comparative example is basically the same as Example 1, except that the silane coupling agent is omitted in this comparative example. In this comparative example, the components include 62% polymer matrix PP, 25% boron nitride, 10% alumina and 3% fluorinated graphene.
[0105] Comparative Example 4
[0106] This comparative example is basically the same as Example 1, except that graphene is used instead of fluorinated graphene in this comparative example.
[0107] Comparative Example 5
[0108] This comparative example is basically the same as Example 1, except that boron nitride and alumina were not pretreated in this comparative example, nor were they coated with silane coupling agent. Instead, boron nitride, alumina and silane coupling agent were directly fed into the feed section of a twin-screw extruder.
[0109] Comparative Example 6
[0110] This comparative example is basically the same as Example 1, except that the fluorinated graphene in this comparative example is fed in one go, rather than in multiple feeds.
[0111] Experimental Example 1
[0112] This experimental example verifies the effect of increased thermal conductivity of the insulating adhesive on cell temperature rise at different rates. Please refer to the simulation results figures. Figure 6 .
[0113] from Figure 6 It can be seen that, Figure 6 The horizontal axis represents thermal conductivity, increasing by 0.2 W / (m·K) each time; the vertical axis represents the difference between the average cell temperature at the corresponding thermal conductivity and the average cell temperature at the current thermal conductivity minus 0.2 W / (m·K). In other words, it represents the amount by which the cell temperature decreases for every 0.2 W / (m·K) increase in thermal conductivity.
[0114] At a C-rate of 0.5, the thermal conductivity of the insulating component is 0.2–1.0 W / (m·K). For every 0.2 W / (m·K) increase in thermal conductivity, the temperature drops by more than 0.1 °C. Beyond 1.0 W / (m·K), each increase in thermal conductivity results in a temperature drop of less than 0.1 °C, rendering it insignificant in engineering terms. At a C-rate of 1, the temperature drops by more than 0.1 °C before reaching 1.2 W / (m·K). Beyond 1.2 W / (m·K), the temperature drops by less than 0.1 °C, rendering it insignificant in engineering terms. At a C-rate of 1.5, the temperature drops by more than 0.1 °C before reaching 1.8 W / (m·K). Beyond 1.8 W / (m·K), the temperature drops by less than 0.1 °C, rendering it insignificant in engineering terms.
[0115] Furthermore, this invention also investigated the effect of increased thermal conductivity of the insulating component on the average temperature of the battery cell; please refer to [link to relevant documentation]. Figure 7 .
[0116] from Figure 7It can be seen that at low rates such as 0.5C, the average cell temperature is less than 30℃ and close to room temperature, so increasing the thermal conductivity of the insulation has little effect on the average cell temperature; or in other words, there is no need to further increase the thermal conductivity of the insulation to reduce the cell temperature. At high rates such as 1.5C, the average cell temperature is already greater than 45℃, and the temperature in some areas such as the adapter plate may have exceeded the specified 55℃. Therefore, considering this situation, it is appropriate to determine how much the thermal conductivity of the insulation should be increased at high rates.
[0117] Based on the above experiments, the composite material in this invention is designed with a thermal conductivity range of 0.5 to 2 W / (m·K), with a preferred range of 0.5 to 1.3 W / (m·K).
[0118] Experimental Example 2
[0119] The materials obtained in Examples 1-5 and Comparative Examples 1-6 were subjected to the following performance tests:
[0120] (1) Thermal conductivity: Laser flash method (ASTM E1461), index ≥0.8W / m·K;
[0121] (2) Insulation resistance: Volume resistivity > 10 15 Ω·cm (GB / T 1410);
[0122] (3) Mass change rate after immersion in electrolyte: At 85℃, after immersion in electrolyte for 8 hours, the weight loss rate is >-3%; high temperature accelerates the reaction, and the weight loss rate ensures that there will be no serious reaction with the electrolyte.
[0123] The test results are as follows:
[0124]
[0125] As can be seen from the table above, the composite material provided in the embodiments of the present invention can maintain a volume resistivity >101 Ω·cm while still achieving a thermal conductivity of 0.88-1.18 W / m·K. Furthermore, the mass change rate after immersion in the electrolyte is small, demonstrating its excellent corrosion resistance, dimensional stability, and safety. In Comparative Example 1, omitting graphene oxide results in a smaller increase in thermal conductivity. In Comparative Example 2, omitting boron nitride and aluminum oxide leads to a smaller increase in thermal conductivity and a significant decrease in insulation. In Comparative Example 3, omitting the silane coupling agent results in poor compatibility between BN / AlO and the polymer matrix, leading to increased resistivity and decreased thermal conductivity. It also introduces interface defects, causing localized electric field concentration and posing a certain risk of breakdown. In Comparative Example 4, graphene is used instead of fluorinated graphene. Due to the higher thermal conductivity of graphene, the thermal conductivity of the composite material is significantly improved, while the resistivity decreases sharply. In Comparative Example 5, neither boron nitride nor alumina was pretreated, nor was a silane coupling agent used for coating. This resulted in poor compatibility between BN / AlO and the polymer matrix, leading to increased resistivity and decreased thermal conductivity. In Comparative Example 6, fluorinated graphene was fed in a single batch, easily forming conductive pathways, which in turn led to decreased resistivity and increased thermal conductivity.
[0126] In summary, the composite material provided by this invention optimizes the synergistic design of the polymer matrix (PC, PET, PP) and thermally conductive particles. In this invention, thermally conductive particles are added to the polymer matrix, increasing the thermal conductivity of the polymer matrix without compromising its insulation properties. Simultaneously, the silane coupling agent improves the compatibility between the thermally conductive particles and the polymer matrix through chemical bonding (reaction of -NH with -OH on the surface of the thermally conductive particles); it also reduces the surface energy of the thermally conductive particles, improves dispersion uniformity, inhibits agglomeration, and reduces interfacial thermal resistance. By combining the above components in specific amounts, a synergistic thermally conductive network can be formed, increasing the thermal conductivity to 0.5–2 W / m·K while ensuring a volume resistivity >10¹ Ω·cm. This invention further specifies the preparation method of the above-mentioned composite material. By pretreating boron nitride and alumina, the compatibility between the filler and the polymer matrix can be enhanced. Furthermore, the multiple additions of fluorinated graphene ensure stepwise blending of the fluorinated graphene with the polymer matrix, boron nitride, and alumina, avoiding the formation of conductive pathways. In addition, the passivation layer improves resistance to electrolyte corrosion. The prepared composite material can be widely used in the manufacture of components for secondary battery cells. It is particularly suitable for manufacturing at least one of the following components: Mylar film 131, bottom plate 140, lower plastic 123, insulating film 133, battery cell insulating tape 134, and top patch 110.
[0127] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A composite material, characterized in that, The composite material comprises a polymer matrix, thermally conductive particles, and a silane coupling agent.
2. The composite material according to claim 1, characterized in that, The mass percentage of the thermally conductive particles is 28%-55%; And / or, the thermal conductivity of the composite material is 0.5 to 2 W / m·K; preferably 0.5 to 1.3 W / m·K; And / or, the polymer matrix includes at least one of PP, PET and PC; And / or, the thermally conductive particles include one or more of boron nitride, aluminum oxide, graphene, aluminum nitride, silicon nitride, silicon carbide, magnesium oxide, zinc oxide, barium titanate, cerium dioxide, Sr2ZnSi2O7, TiC, TiO2, and Al(OH)3.
3. The composite material according to claim 2, characterized in that, The thermally conductive particles include boron nitride, aluminum oxide, and graphene, wherein the graphene is fluorinated graphene; the components of the composite material, by mass percentage, include 50%-70% polymer matrix, 20-30% boron nitride, 5%-15% aluminum oxide, 3%-10% fluorinated graphene, and 1%-3% silane coupling agent.
4. The composite material according to claim 3, characterized in that, The boron nitride is in the form of flakes with a particle size of 1-5 μm; And / or, the alumina is spherical with a particle size of 0.5-2 μm; And / or, the C / F ratio of the fluorinated graphene is ≥4:1, and the thickness of the fluorinated graphene is 1-5 nm; And / or, the volume resistivity of the composite material is >101 Ω·cm.
5. A method for preparing a composite material, characterized in that, It includes melt-blending the components of the composite material as described in any one of claims 1-4, followed by extrusion and compression molding, and plasma treatment of the molded sample to form a passivation layer.
6. The method for preparing the composite material according to claim 5, characterized in that, Before the melt blending, the thermally conductive particles are pretreated: the thermally conductive particles are first mixed and dried to obtain a dried material, and then the dried material is coated with a solution of the silane coupling agent to obtain a premix. Preferably, the drying process includes drying at 110-130°C for 3-5 hours.
7. The method for preparing the composite material according to claim 6, characterized in that, The melt blending includes: feeding the polymer matrix and the premix into a twin-screw extruder for melting; Preferably, the screw speed of the twin-screw extruder is 200-300 rpm; Preferably, the twin-screw extruder is provided with a feeding section, a melting section, and a mixing section, wherein the temperature of the feeding section is 180-250℃, the temperature of the melting section is 200-280℃, and the temperature of the mixing section is 190-260℃; Preferably, when the thermally conductive particles include boron nitride, aluminum oxide, and fluorinated graphene, the boron nitride and aluminum oxide are first mixed and dried to obtain a dried material, and the dried material is coated with a solution of the silane coupling agent to obtain a premix; then the polymer matrix and the premix are fed into a twin-screw extruder for melting, and then the fluorinated graphene is added in multiple batches for melt blending.
8. The method for preparing the composite material according to claim 5, characterized in that, The pressing temperature is 180-250℃, the pressure is 10-20MPa, and the holding time is 5-10min. And / or, the plasma treatment includes treating with Ar gas at a power of 80-120W for 4-6 minutes to generate a passivation layer of 5-10 nm.
9. The application of the composite material as described in any one of claims 1-4 or the composite material prepared by the method described in any one of claims 5-8 in the manufacture of parts for secondary battery cells; Preferably, the components of the secondary battery cell include at least one of Mylar film, bottom plate, lower plastic, insulating film, battery cell insulating tape, and top patch; the thermal conductivity of the composite material is 0.5 to 2 W / m·K.
10. A secondary battery cell, characterized in that, It comprises, from top to bottom, a top patch, a top cover, a core, and a bottom support plate. The outer side of the core is covered with a Mylar film, an aluminum shell, and an insulating film. The core is provided with battery cell insulating tape for fixing, insulating, and heat transfer. The top cover comprises a top cover sheet and a lower plastic sheet. At least one of the Mylar film, bottom support plate, lower plastic sheet, insulating film, battery cell insulating tape, and top patch is made of the composite material described in any one of claims 1-4.